Method for extracting lithium from salt lake brine based on selective adsorbent
By using modified montmorillonite and epoxy curing agent in the salt lake brine, the problems of low adsorption capacity, poor selectivity and poor use stability are solved, and the lithium ions in the salt lake brine are efficiently extracted.
Patent Information
- Application Number
- CN202510383998.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-28
AI Technical Summary
The existing adsorption method has problems such as low adsorption capacity, poor selectivity and poor use stability when extracting lithium ions in salt lake brine.
Lithium ion adsorbent with high adsorption capacity and selectivity were prepared by mixing alkyl ammonium bromide and montmorillonite and compounding with polyethylene glycol diglycidyl ether and epoxy curing agent.
The adsorption capacity and desorption rate of lithium ions are significantly improved, the adsorption selectivity and use stability are improved, and the efficient extraction of lithium ions in salt lake brine is achieved.
Smart Images

Figure CN119876644A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for extracting lithium from salt lake brine based on a selective adsorbent, belonging to the technical field of extracting lithium from salt lakes. Background Art
[0002] Lithium is widely used in modern industrial production and has a large market demand, making the development of lithium resources particularly important. Lithium resources in nature exist mainly in two forms, one in solid minerals (such as spodumene, petalite, lithium mica, etc.), and the other in liquid minerals (such as salt lake brine, underground brine). Among them, the salt lake brine in the liquid mineral contains a large amount of lithium resources. However, most of the lithium resources in the salt lake brine belong to brines with a high magnesium-lithium ratio and a low lithium content. Therefore, how to efficiently extract lithium from salt lake brine has always been a research hotspot.
[0003] At present, the main technologies for extracting lithium from salt lake brine include precipitation, solvent extraction, evaporation crystallization, adsorption, etc. Among them, the adsorption method is considered to be a more promising method for extracting lithium. The adsorption method refers to the physical and chemical reaction between the solute and the adsorbent to form a strong chemical bond, hydrogen bond, surface coordination, imprinting, screening and electrostatic action. The adsorption method is suitable for recovering lithium from low-grade lithium-containing salt lake brine. At present, common inorganic lithium adsorbents include manganese ion sieves and aluminum salt adsorbents. For example, Chinese patent document CN112777614B uses a dilute acid solution to pre-desorb the manganese ion sieve adsorbent, and utilizes the characteristics of different sodium and lithium desorption orders to achieve the desorption of most of the sodium and a small part of the lithium first, and then uses a dilute acid solution to desorb the adsorbent, so as to achieve the purpose of reducing the sodium and lithium in the qualified liquid, but the sodium-lithium ratio in the desorbed solution obtained is at least 0.5, and the adsorption selectivity between lithium and sodium is biased. In addition, when using manganese lithium adsorbents, alkaline environment adsorption and acidic environment desorption are required, which consumes a large amount of acid and alkali solution, and the dissolution loss is very serious. Although aluminum salt adsorbents have good selectivity, their lithium ion adsorption capacity is low, only 0.6-0.9 mg / g. Therefore, it is urgent to develop a method for extracting lithium from salt lake brine that has high adsorption capacity, high selectivity and good stability. Summary of the invention
[0004] The purpose of the present invention is to provide a method for extracting lithium from salt lake brine based on a selective adsorbent, so as to solve the problems of low adsorption capacity, poor selectivity and poor stability in use when extracting lithium ions from salt lakes by adsorption methods.
[0005] The present invention provides a method for extracting lithium from salt lake brine based on a selective adsorbent, comprising the following steps: (1) mixing alkylammonium bromide and montmorillonite in water at 60-80° C. for 2-6 hours, separating the solid from the liquid, and washing the separated solid with water until no bromide ions are present in the washing liquid, thereby obtaining an organic montmorillonite; the alkylammonium bromide is dodecyltrimethylammonium bromide, tridecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, pentadecyltrimethylammonium bromide or hexadecyltrimethylammonium bromide; and the mass ratio of the alkylammonium bromide to the montmorillonite is 25-30:100; (2) Mixing polyethylene glycol diglycidyl ether and an organic montmorillonite dispersion at 60-75° C. and refluxing for 2-6 hours, then removing the solvent, drying, and grinding to obtain intercalated montmorillonite; the mass of the polyethylene glycol diglycidyl ether is 5-10% of the mass of the organic montmorillonite; and the number average molecular weight of the polyethylene glycol diglycidyl ether is 600-1000; (3) heating the intercalated montmorillonite and the epoxy curing agent to 95-105° C. in a solvent under the action of a catalyst, mixing and reacting for 6-8 hours, then removing the solvent and grinding to obtain a lithium ion adsorbent; the epoxy curing agent is a benzo-12-crown-4 dicarboxylic acid compound or is composed of a benzo-12-crown-4 dicarboxylic acid compound and a boroxine tricarboxylic acid compound in a mass ratio of 5:0.1-0.4; the structural formula of the benzo-12-crown-4 dicarboxylic acid compound is as follows: ; The structural formula of the boroxine tricarboxylic acid compound is as follows: ; (4) A lithium ion adsorbent is used to adsorb lithium ions in salt lake brine, and then acid washing is performed to desorb lithium ions from the lithium ion adsorbent into acid solution, and finally the lithium ions in the acid solution are recovered and extracted.
[0006] Preferably, the montmorillonite in step (1) is used in the form of a montmorillonite dispersion, and the mass fraction of the montmorillonite dispersion is 5-10%.
[0007] Preferably, the average particle size of the montmorillonite in step (1) is 15-30 μm.
[0008] Preferably, the mixing method in step (1) is as follows: adding alkylammonium bromide to the montmorillonite dispersion and then performing the mixing.
[0009] Preferably, the mixing and refluxing method in step (2) is as follows: dissolving polyethylene glycol diglycidyl ether in acetone to obtain a polyethylene glycol diglycidyl ether solution with a mass fraction of 40-50%; and then mixing and refluxing the polyethylene glycol diglycidyl ether solution and an organic montmorillonite dispersion with a mass fraction of 5-10%.
[0010] Preferably, the average particle size of the intercalated montmorillonite is 20-40 μm.
[0011] Preferably, in step (3), under nitrogen protection, the intercalated montmorillonite is dispersed in N,N-dimethylformamide to obtain an intercalated montmorillonite dispersion with a mass fraction of 10-15%, and then an epoxy curing agent is added, and then the heating is performed.
[0012] Preferably, in step (3), the average particle size of the lithium ion adsorbent is 20-30 μm.
[0013] Preferably, in step (3), the boroxine tricarboxylic acid compound is prepared by reacting 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride and thioglycolic acid; the molar ratio of 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride to thioglycolic acid is 1:3.1-3.5.
[0014] Preferably, in step (3), the preparation method of the boroxine tricarboxylic acid compound is as follows: 4-carboxyphenylboronic acid and thionyl chloride in a molar ratio of 1:20 are mixed for 50 minutes, then the temperature is raised to 80°C, mixed and reacted for 20 hours, excess thionyl chloride is removed, and 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride is obtained after drying; then 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride is fully dissolved In dichloromethane, a solution with a mass fraction of 5-10% is obtained, and then at 0-5°C, a dichloromethane solution of 5-10% thioglycolic acid is added dropwise to the 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride solution, and then triethylamine is added. The mixture is stirred and reacted at 0-5°C for 5-8h, filtered, and the filtrate is rotary evaporated, washed with water to remove unreacted thioglycolic acid, and dried to obtain a boroxine tricarboxylic acid compound.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses alkylammonium bromide to modify montmorillonite, thereby increasing the interlayer distance of montmorillonite and improving its specific surface area. Then, polyethylene glycol diglycidyl ether is used to modify the montmorillonite again, and the polyethylene glycol diglycidyl ether can be inserted into the montmorillonite layer by using the oxygen atoms in its molecular chain through hydrogen bonding and molecular chain entanglement. Finally, an epoxy curing agent containing a crown ether is used to react with the modified montmorillonite, so that the crown ether group is chemically bonded to the inside and outside of the montmorillonite layer, thereby improving the uniformity of the distribution of the crown ether group, thereby improving the adsorption amount and adsorption selectivity of the adsorbent for lithium ions.
[0016] (2) The present invention can significantly improve the adsorption capacity and desorption rate of the adsorbent for lithium ions by using carboxyl crown ether and boroxine tricarboxylic acid compound as a composite curing agent. This may be because the boroxine tricarboxylic acid compound can improve the crosslinking degree of the epoxy resin on the one hand, and introduce a large number of boroxine structures on the other hand to increase the adsorption sites of lithium ions. In addition, due to the cyclic structure of boroxine, it can play a synergistic role with the cyclic crown ether to jointly adsorb lithium ions and improve the adsorption capacity of lithium ions. In addition, boroxine is hydrophobic and can form a good amphiphilic structure with the epoxy resin after ring opening to form polyhydroxyl groups, thereby improving the surface activity, thereby improving the migration rate of lithium ions and reducing their movement barriers, thereby further improving the adsorption capacity and desorption rate of lithium ions.
[0017] (3) The present invention utilizes an adsorbent having good adsorption capacity, reusability and good adsorption selectivity for lithium ions to adsorb lithium ions in salt lake brine, and desorbs the lithium ions through acid solution to allow the lithium ions to enter the acid solution, thereby realizing the extraction and utilization of lithium ions in salt lake brine, which has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is the H NMR spectrum of the benzo-12-crown-4 dicarboxylic acid compound of the present invention; Figure 2 This is the H NMR spectrum of the boroxine tricarboxylic acid compound in Example 3 of the present invention. DETAILED DESCRIPTION
[0019] The following examples are intended to further illustrate the present invention rather than to limit the scope of protection of the present invention.
[0020] The preparation method of the benzo-12-crown-4 dicarboxylic acid compound used in the present invention is as follows: (1) Dissolve 0.01 mol of benzo-12-crown-4 in 25 mL of chloroform, cool to -5°C under nitrogen protection, then add 0.1 mol of chlorosulfonic acid dropwise. After the addition is complete, continue stirring at room temperature for 6 h. Pour the reaction mixture into ice water, let stand and separate the layers. Concentrate the organic phase by rotary evaporation and crystallize it with n-heptane to obtain benzo-12-crown-4sulfonyl chloride.
[0021] (2) 5-hydroxymethyl-1,3-benzoic acid (as shown in Formula 1) and dichloromethane are stirred evenly to obtain a solution with a mass fraction of 5%, and then a chloroform solution of benzo-12-crown-4sulfonyl chloride with a mass fraction of 5% is added dropwise at 0°C. After the addition is completed, triethylamine is added (the molar ratio of 5-hydroxymethyl-1,3-benzoic acid, benzo-12-crown-4sulfonyl chloride and triethylamine is 1:1:1.2), and then stirred at 5°C for 10 hours, filtered, and the filtrate is rotary evaporated and dried to obtain a benzo-12-crown-4 dicarboxylic acid compound (as shown in Formula 2), whose H NMR spectrum is shown in Figure 1 shown.
[0022]
[0023] Formula 1
[0024] Formula 2 Example 1
[0025] The method for extracting lithium from salt lake brine based on a selective adsorbent of this embodiment comprises the following steps: (1) Disperse montmorillonite with an average particle size of 15 μm in deionized water to obtain a montmorillonite dispersion with a mass fraction of 10%.
[0026] (2) Tetradecyltrimethylammonium bromide is added to the montmorillonite dispersion in a mass ratio of tetradecyltrimethylammonium bromide to montmorillonite of 30:100, and then stirred at 60°C for 6 hours, filtered, and the filter cake is washed with water until no bromide ions are left in the washing liquid, thereby obtaining an organic montmorillonite.
[0027] (3) Organic montmorillonite was dispersed in deionized water to obtain an organic montmorillonite dispersion with a mass fraction of 5%; polyethylene glycol diglycidyl ether (number average molecular weight of 800) was dissolved in acetone to obtain a polyethylene glycol diglycidyl ether solution with a mass fraction of 40%; the polyethylene glycol diglycidyl ether solution and the organic montmorillonite dispersion were stirred and refluxed at 60°C for 6 hours, and then the solvent was removed by rotary evaporation, dried, and ground to obtain intercalated montmorillonite with an average particle size of 20 μm; the mass of polyethylene glycol diglycidyl ether in the polyethylene glycol diglycidyl ether solution was 5% of the mass of the organic montmorillonite in the organic montmorillonite dispersion.
[0028] (4) Under nitrogen protection, the intercalated montmorillonite was dispersed in N,N-dimethylformamide to obtain an intercalated montmorillonite dispersion with a mass fraction of 10%, and then an epoxy curing agent (the epoxy curing agent is a benzo-12-crown-4 dicarboxylic acid compound, and the molar amount of the carboxyl group in the epoxy curing agent is equal to the molar amount of the epoxy group in the intercalated montmorillonite) and a catalyst (the catalyst is triethylbenzylammonium bromide, and the mass of the catalyst is 1% of the mass of the epoxy curing agent) were added, heated to 95°C, stirred for reaction for 8 hours, cooled to room temperature after the reaction was completed, vacuum dried at 80°C to remove the solvent, and then ground to obtain a lithium ion adsorbent with an average particle size of 30 μm.
[0029] (5) A lithium ion adsorbent is used to adsorb lithium ions in salt lake brine, and then the lithium ion adsorbent that has adsorbed lithium ions is acid-washed to desorb lithium ions from the lithium ion adsorbent and enter an acid solution, and then the lithium ions in the acid solution are recovered and extracted. Example 2
[0030] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 1 is that the epoxy curing agent in step (4) of the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment is composed of benzo-12-crown-4 dicarboxylic acid compound and 4-carboxyphenylboric acid in a mass ratio of 5:0.3. Example 3
[0031] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of the present embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 1 is that the epoxy curing agent in step (4) of the method for extracting lithium from salt lake brine based on selective adsorbent of the present embodiment is composed of a benzo-12-crown-4 dicarboxylic acid compound and a boroxine tricarboxylic acid compound in a mass ratio of 5:0.2, and the preparation method of the boroxine tricarboxylic acid compound is as follows: 4-carboxyphenylboronic acid and thionyl chloride in a molar ratio of 1:20 are added to a reaction kettle, and then nitrogen is introduced into the reaction kettle, stirred at room temperature for 50 minutes, and then heated to 80° C., stirred for reaction for 20 hours, and the excess thionyl chloride is removed by reduced pressure distillation. After vacuum drying, a white powder solid is obtained, namely 4,4′,4″-(boroxine-2 ,4,6)-tribenzoyl chloride; then 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride is fully dissolved in dichloromethane to obtain a 5% solution by mass, and then at 0°C, a 5% solution of thioglycolic acid in dichloromethane is added dropwise to the 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride solution, the molar ratio of thioglycolic acid to 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride is 3.5:1, and then triethylamine is added (the molar amount of triethylamine is equal to the molar amount of thioglycolic acid), stirred and reacted at 0°C for 8h, filtered, the filtrate is rotary evaporated, washed with water to remove unreacted thioglycolic acid, and dried to obtain a boroxine tricarboxylic acid compound (the nuclear magnetic hydrogen spectrum of the boroxine tricarboxylic acid compound is as shown in Figure 2 The structural formula is shown below: . Example 4
[0032] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 3 is that the epoxy curing agent in step (4) of the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment is composed of a benzo-12-crown-4 dicarboxylic acid compound and a boroxine tricarboxylic acid compound in a mass ratio of 5:0.1. Example 5
[0033] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 3 is that the epoxy curing agent in step (4) of the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment is composed of a benzo-12-crown-4 dicarboxylic acid compound and a boroxine tricarboxylic acid compound in a mass ratio of 5:0.4. Example 6
[0034] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of the present embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 3 is that the tetradecyltrimethylammonium bromide in step (2) of the method for extracting lithium from salt lake brine based on selective adsorbent of the present embodiment is replaced by hexadecyltrimethylammonium bromide. Example 7
[0035] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of the present embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 3 is that the tetradecyltrimethylammonium bromide in step (2) of the method for extracting lithium from salt lake brine based on selective adsorbent of the present embodiment is replaced by dodecyltrimethylammonium bromide. Example 8
[0036] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent in this embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent in Example 3 is that the number average molecular weight of polyethylene glycol diglycidyl ether in step (3) of the method for extracting lithium from salt lake brine based on selective adsorbent in this embodiment is 600. Example 9
[0037] The difference between the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment and the method for extracting lithium from salt lake brine based on selective adsorbent of Example 3 is that the number average molecular weight of polyethylene glycol diglycidyl ether in step (3) of the method for extracting lithium from salt lake brine based on selective adsorbent of this embodiment is 1000.
[0038] Comparative Example 1 The difference between the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example and the method for extracting lithium from salt lake brine based on selective adsorbent in Example 3 is that the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example omits steps (1) to (2), and directly disperses montmorillonite with an average particle size of 15 μm in deionized water to obtain a montmorillonite dispersion with a mass fraction of 10%; and then stirs and refluxes the polyethylene glycol diglycidyl ether solution and the montmorillonite dispersion.
[0039] Comparative Example 2 The difference between the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example and the method for extracting lithium from salt lake brine based on selective adsorbent in Example 3 is that step (3) is omitted in the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example, and the intercalated montmorillonite in step (4) is replaced by the organic montmorillonite obtained in step (2).
[0040] Comparative Example 3 The difference between the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example and the method for extracting lithium from salt lake brine based on selective adsorbent in Example 3 is that the number average molecular weight of polyethylene glycol diglycidyl ether in step (3) of the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example is 200.
[0041] Comparative Example 4 The difference between the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example and the method for extracting lithium from salt lake brine based on selective adsorbent in Example 3 is that the number average molecular weight of polyethylene glycol diglycidyl ether in step (3) of the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example is 2000.
[0042] Comparative Example 5 The difference between the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example and the method for extracting lithium from salt lake brine based on selective adsorbent in Example 3 is that the epoxy curing agent in step (4) of the method for extracting lithium from salt lake brine based on selective adsorbent in this comparative example is a boroxine tricarboxylic acid compound.
[0043] Effect Example 1 In order to evaluate the adsorption effect of the lithium ion adsorbent in the embodiments and comparative examples, 0.1 g of the lithium ion adsorbent was weighed and placed in a 250 mL flask, and then 100 mL of a lithium salt solution (the lithium salt solution was a lithium chloride solution with a lithium ion concentration of 100 mg / L) was added. The flask was then placed in a constant temperature water bath shaker at a temperature of 30°C and a rotation speed of 120 r / min. The upper clear liquid was continuously removed and the concentration of lithium ions therein was determined until the adsorption reached equilibrium. According to the change in the concentration of lithium ions in the solution before and after adsorption, the saturated adsorption amount X1 of the lithium ion adsorbent for lithium ions was calculated. In addition, the lithium ion adsorbent that has reached lithium ion adsorption saturation is placed in a 250mL flask, and then 150mL of hydrochloric acid with a concentration of 0.3mol / L is added. The flask is sealed with plastic wrap, and then placed in a constant temperature water bath shaker at a temperature of 25°C and a speed of 120r / min for oscillation desorption and desorption. After 8 hours, the desorption is completed, the upper clear liquid is removed, and the concentration of lithium ions therein is determined. According to the change in the concentration of lithium ions in hydrochloric acid before and after desorption, the desorption rate of lithium ions is calculated. The desorption rate is equal to the ratio of the mass of lithium ions desorbed from the lithium ion adsorbent that has reached lithium ion adsorption saturation to the mass of lithium ions in the lithium ion adsorbent that has reached lithium ion adsorption saturation. Finally, the lithium ion adsorbent is repeatedly cycled for saturated lithium adsorption and desorption and desorption of lithium ions according to the above method, and the saturated adsorption amount of lithium ions by the adsorbent after the 10th desorption and desorption of lithium ions is recorded X10. The saturated adsorption amount X1 of lithium ions by the lithium ion adsorbent in each embodiment and comparative example, the lithium ion desorption rate and the saturated adsorption amount X10 of lithium ions by the adsorbent after the 10th desorption of lithium ions are shown in Table 1.
[0044] Table 1 Saturated adsorption capacity of lithium ions by lithium ion adsorbents in various embodiments and comparative examples Lithium ion desorption rate and saturated adsorption capacity of lithium ions by the adsorbent after the 10th desorption of lithium ions Lithium ion adsorbent Saturated adsorption capacity X1 (mg / g) Desorption rate (%) Saturated adsorption capacity X10 (mg / g) Example 1 16 92.1 12 Example 2 18 91.8 15 Example 3 35 99.2 34 Example 4 28 98.5 26 Example 5 27 98.7 26 Example 6 25 97.2 20 Example 7 24 97.6 18 Example 8 32 98.9 31 Example 9 36 99.4 35 Comparative Example 1 5 85.2 3 Comparative Example 2 3 86.7 2 Comparative Example 3 13 84.3 8 Comparative Example 4 11 85.8 7 Comparative Example 5 0.5 81.2 0.4 As shown in Table 1, the adsorption material prepared by using benzo-12-crown-4 dicarboxylic acid compound alone as epoxy curing agent in Example 1 has a higher adsorption capacity and desorption rate for lithium ions. When benzo-12-crown-4 dicarboxylic acid compound and 4-carboxyphenylboronic acid are used together as epoxy curing agents in Example 2, the adsorption capacity of the adsorption material prepared by using benzo-12-crown-4 dicarboxylic acid compound and 4-carboxyphenylboronic acid as epoxy curing agents is improved, which may be because the introduction of boron element can increase the adsorption sites of lithium ions. When the boroxine tricarboxylic acid compound curing agent is introduced in Examples 3-5, the adsorption capacity and desorption rate of the prepared adsorption material for lithium ions are significantly improved. This may be because the boroxine tricarboxylic acid compound can, on the one hand, increase the crosslinking degree of the epoxy resin, and on the other hand, introduce a large number of boroxine structures to increase the adsorption sites of lithium ions. In addition, due to the cyclic structure of boroxine, it can play a synergistic role with the cyclic crown ether to jointly adsorb lithium ions and improve the adsorption capacity of lithium ions. In addition, boroxine is hydrophobic and can form a good amphiphilic structure with the epoxy resin after ring opening to form polyhydroxy groups, thereby improving the surface activity, thereby increasing the migration rate of lithium ions and reducing their movement barriers, thereby further improving the adsorption capacity and desorption rate of lithium ions. In addition, according to Examples 3-5, as the amount of the boroxine tricarboxylic acid compound increases, the adsorption capacity and desorption rate of the prepared adsorbent material for lithium ions show a trend of first increasing and then decreasing. This may be because when the amount of the boroxine tricarboxylic acid compound is small, it is not enough to play its role. When the amount of the boroxine tricarboxylic acid compound is too much, the cross-linked structure is too dense, which is not conducive to the development of the active structure during the adsorption process of montmorillonite, affecting the adsorption and desorption process. From Comparative Examples 1-2, it can be seen that the use of ammonium bromide to modify montmorillonite can increase the adsorption capacity and desorption rate of the adsorbent material for lithium ions, because ammonium bromide can open the montmorillonite structure and increase its specific surface area; and the use of polyethylene glycol diglycidyl ether to modify montmorillonite can also increase the adsorption capacity and desorption rate of the adsorbent material for lithium ions, because polyethylene glycol diglycidyl ether can be inserted into montmorillonite, providing chemical bonding stable sites for subsequent crown ethers and boroxine, thereby increasing the adsorption capacity and desorption rate of lithium ions. According to Comparative Examples 3-4, the molecular weight of polyethylene glycol diglycidyl ether affects the adsorption capacity and desorption rate of lithium ions, which may be due to the fact that the molecular weight of polyethylene glycol diglycidyl ether is too large or too small, which is not conducive to the insertion into montmorillonite and the subsequent introduction of crown ether and boroxine structures with suitable chain lengths. In addition, according to Examples 3 and 6-7, it can be seen that the carbon chain length of ammonium bromide affects the adsorption capacity and desorption rate of lithium ions, which may be due to the fact that the carbon chain length affects the modification of montmorillonite and the subsequent introduction of crown ether and boroxine structures with suitable chain lengths.
[0045] Effect Example 2 In order to evaluate the adsorption selectivity of lithium ions by the lithium ion adsorbent in the embodiments and comparative examples, 0.1g of lithium ion adsorbent was weighed and placed in a 250mL flask, and then 100mL of simulated salt lake brine was added (the simulated salt lake brine was prepared by mixing sodium chloride, magnesium chloride, potassium chloride, lithium chloride, calcium chloride and water, and the concentration of sodium element was 1200mg / L, the concentration of magnesium element was 2000mg / L, the concentration of potassium element was 600mg / L, the concentration of lithium element was 50mg / L, and the concentration of calcium element was 80mg / L), and then placed in a constant temperature water bath shaker at a temperature of 30°C and a speed of 120r / min. After 24 hours, the concentration of each metal ion was determined, and the adsorption amount of each metal ion by the lithium ion adsorbent was calculated according to the change in the concentration of metal ions in the solution before and after adsorption. The adsorption amount of each metal ion by the lithium ion adsorbent in each embodiment and comparative example is shown in Table 2.
[0046] Table 2 Adsorption amount of each metal ion by the lithium ion adsorbent in each embodiment and comparative example
[0047] It can be seen from Table 2 that the adsorbents used in the embodiments of the present invention have good selective adsorption of lithium ions, which is significantly better than the selective adsorption of lithium ions by the adsorbents in the comparative examples, and can be used for the extraction of lithium ions from salt lake brine.
Claims
1. A method for extracting lithium from salt lake brine based on a selective adsorbent, characterized in that: The following steps are involved: (1) mixing alkylammonium bromide and montmorillonite in water at 60-80° C. for 2-6 hours, separating the solid from the liquid, and washing the separated solid with water until no bromide ions are present in the washing liquid, thereby obtaining an organic montmorillonite; the alkylammonium bromide is dodecyltrimethylammonium bromide, tridecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, pentadecyltrimethylammonium bromide or hexadecyltrimethylammonium bromide; and the mass ratio of the alkylammonium bromide to the montmorillonite is 25-30:100; (2) Mixing polyethylene glycol diglycidyl ether and an organic montmorillonite dispersion at 60-75° C. and refluxing for 2-6 hours, then removing the solvent, drying, and grinding to obtain intercalated montmorillonite; the mass of the polyethylene glycol diglycidyl ether is 5-10% of the mass of the organic montmorillonite; and the number average molecular weight of the polyethylene glycol diglycidyl ether is 600-1000; (3) heating the intercalated montmorillonite and the epoxy curing agent to 95-105° C. in a solvent under the action of a catalyst, mixing and reacting for 6-8 hours, then removing the solvent and grinding to obtain a lithium ion adsorbent; the epoxy curing agent is a benzo-12-crown-4 dicarboxylic acid compound or is composed of a benzo-12-crown-4 dicarboxylic acid compound and a boroxine tricarboxylic acid compound in a mass ratio of 5:0.1-0.4; the structural formula of the benzo-12-crown-4 dicarboxylic acid compound is as follows: ; The structural formula of the boroxine tricarboxylic acid compound is as follows: ; (4) A lithium ion adsorbent is used to adsorb lithium ions in salt lake brine, and then acid washing is performed to desorb lithium ions from the lithium ion adsorbent into acid solution, and finally the lithium ions in the acid solution are recovered and extracted.
2. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: The montmorillonite in step (1) is used in the form of a montmorillonite dispersion, and the mass fraction of the montmorillonite dispersion is 5-10%.
3. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: The average particle size of the montmorillonite in step (1) is 15-30 μm.
4. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 2, characterized in that: The mixing method in step (1) is as follows: adding alkylammonium bromide to the montmorillonite dispersion and then performing the mixing.
5. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: The mixing and refluxing method in step (2) is as follows: dissolving polyethylene glycol diglycidyl ether in acetone to obtain a polyethylene glycol diglycidyl ether solution with a mass fraction of 40-50%; then mixing and refluxing the polyethylene glycol diglycidyl ether solution and an organic montmorillonite dispersion with a mass fraction of 5-10%.
6. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: The average particle size of intercalated montmorillonite is 20~40μm.
7. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: In step (3), under nitrogen protection, the intercalated montmorillonite is dispersed in N,N-dimethylformamide to obtain an intercalated montmorillonite dispersion with a mass fraction of 10-15%, and then an epoxy curing agent is added, and then the heating is performed.
8. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: In step (3), the average particle size of the lithium ion adsorbent is 20-30 μm.
9. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 1, characterized in that: In step (3), the boroxine tricarboxylic acid compound is prepared by reacting 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride and thioglycolic acid; the molar ratio of 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride to thioglycolic acid is 1:3.1-3.
5.
10. The method for extracting lithium from salt lake brine based on a selective adsorbent as claimed in claim 9, characterized in that: In step (3), the preparation method of the boroxine tricarboxylic acid compound is as follows: 4-carboxyphenylboronic acid and thionyl chloride in a molar ratio of 1:20 are mixed for 50 minutes, then the temperature is raised to 80° C., mixed and reacted for 20 hours, excess thionyl chloride is removed, and 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride is obtained after drying; then 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride is fully dissolved in dichloride. The reaction mixture is prepared by adding 5-10% thioglycolic acid in dichloromethane to a 4,4′,4″-(boroxine-2,4,6)-tribenzoyl chloride solution at 0-5°C, and then adding triethylamine. The mixture is stirred at 0-5°C for 5-8h and filtered. The filtrate is evaporated and washed with water to remove unreacted thioglycolic acid. The boroxine tricarboxylic acid compound is obtained after drying.
Citation Information
Patent Citations
A method and apparatus for lithium extraction by adsorption from salt lake brine
CN112777614B
Preparation method for high-efficiency recyclable lithium extraction film material for salt lake brine
CN110862631A
Preparation method of H12MDA with low trans-trans isomer content and used catalyst
CN119425676A
Epoxy silane oligomer and coating composition containing same
US20060225612A1
Composites Comprising Polymer and Mesoporous Silicate
US20110281993A1
Cited By
Large-tonnage insulating pull rod joint adhesive and preparation method thereof
CN120682741A
Nickel-based porous adsorption material as well as preparation method and application thereof
CN121060473A